Effects of Antivortex Structures Installed on Trapezoidal Labyrinth Side Weirs on Discharge Capacity and Scouring - Emiroglu, M. Emin; Gogus, Mustafa; Tunc, Mustafa; Islamoglu, Kadir (Asce-Amer Soc Civil Engineers, 2017)
Greater or more constant discharge can be achieved at lower upstream water depths over the weir crest by increasing the effective lengths of labyrinth side weirs. Labyrinth weirs have unevenly shaped crests, resulting in greater crest lengths at the weir opening. Labyrinth side weirs have significant advantages over conventional weirs. For example, the discharge capacities of labyrinth side weirs are 1.5-4.5 times that of conventional side weirs. In this study, the effects of using an antivortex structure in trapezoidal labyrinth side weirs on discharge capacity and scouring were investigated for varying values of Froude number (F-1), dimensionless crest height (p/y(1)), dimensionless weir opening length (L / B), dimensionless effective crest length (L/L-ef), and side wall angle (alpha). First, using data from 537 experimental runs, the antivortex structures that most increased the discharge capacity were determined. Next, the optimum location and dimension of the antivortex structure were investigated. Based on 242 test runs, it was found that as the dimensions of the antivortex structure increased and as the antivortex structure moved toward the center of the weir opening, the discharge coefficient (C-d) increased by approximately 48%. Lastly, clear-water scour experiments were conducted using three antivortex structures with different trapezoidal labyrinth side weir flow intensities. The findings demonstrate that antivortex structures decrease scour depth around the water intake region. (C) 2017 American Society of Civil Engineers.
Keywords: Weir; Antivortex; Discharge coefficient; Labyrinth side weir; Scour